Cellular hormetic response to 27-hydroxycholesterol promotes neuroprotection through AICD induction of MAST4 abundance and kinase activity. Issue 1 (December 2017) - Gongol, Brendan; Marin, Traci; Jeppson, John; Mayagoitia, Karina; Shin, Samuel; Sanchez, Nicholas; Kirsch, Wolff; Vinters, Harry; Wilson, Christopher; Ghribi, Othman; Soriano, Salvador
Abstract The function of the amyloid precursor protein (APP) in brain health remains unclear. This study elucidated a novel cytoprotective signaling pathway initiated by the APP transcriptionally active intracellular domain (AICD) in response to 27-hydroxycholesterol (27OHC), an oxidized cholesterol metabolite associated with neurodegeneration. The cellular response to 27OHC was hormetic, such that low, but not high, doses promoted AICD transactivation of microtubule associated serine/threonine kinase family member 4 (MAST4). MAST4 in turn phosphorylated and inhibited FOXO1-dependent transcriptional repression of rhotekin 2 (RTKN2), an oxysterol stress responder, to optimize cell survival. A palmitate-rich diet, which increases serum 27OHC, or APP ablation, abrogated this responsein vivo . Further, this pathway was downregulated in human Alzheimer's Disease (AD) brains but not in frontotemporal dementia brains. These results unveil MAST4 as functional kinase of FOXO1 in a 27OHC AICD-driven, hormetic pathway providing insight for therapeutic approaches against cholesterol associated neuronal disorders.